Does parent-child connectedness influence substance use among Bhutanese adolescents: evidence from a national survey? - Md. Tanvir Hasan Sojib; Md. Habibur Rahman; Md. Imamur Rashid Gogon; Md. Khalid Hasan (BMC Public Health)
Highlights • Tobacco use was highest, followed by alcohol and marijuana use. • The prevalence of substance use was higher in male than female adolescents. • Parental homework supervision significantly lowered the odds of alcohol and tobacco use. • Parental free-time supervision significantly reduced the odds of alcohol and tobacco use. • No significant association was found between parent-child connectedness and marijuana use.